Factors that drive consumers to green purchase intention among UiTM Malacca City Campus students / Sarjana Siliyu - Siliyu, Sarjana (Faculty of Business and Management, 2018)
Over the last decade, consumer consumption of goods and services has increased tremendously across the world, leading to depletion of natural resources and severe damage to the environment (Chen and Chai, 2010). According to Hossein Nezakati and Masoumeh Hosseinpour (2015) in Malaysia, the concept of environmentally friendly is new. The Malaysian government has invested to protection of the environment. However, the knowledge on consumers’ attitude towards the green products is not high. Although many studies explored the different aspects of green brand (Kilbourne, 2008; Polonsky, 1994), there is a lack of empirical studies about how to increase customers’ intentions to use green products among Malaysian users. The aim of this study was to determine what ar the main reasons that drive the consumers to the intention of green purchase among UiTM Malacca City Campus students. There were four independent variables that included in this study which are green purchase attitude, green perceived value, green perceived trust and ecological knowledge. Meanwhile, green purchase intention was the dependent variable. Based on the findings from the results, it was showed that only green perceived value that had significant impact on the consumers in UiTM Malacca City Campus to the intention toward green purchase. The remaining independent variable has no relationship on green buying intention. To further add, most of the respondents had experience in bought green products. Nevertheless, bottles and accessories were most of the respondents favourite green product includes recycled toilet tissue and recycled paper.